Location of manufacturing FDI in Hungary: How important are inter-company relationships? - Gábor Békés (Magyar Nemzeti Bank, 2005)
In a new economic geography framework with input-output linkages, this study analyses decisions made by foreign firms about their location within Hungary. These firm-to-firm contacts are modelled by creating several corporate customer and supplier access measures for all new foreign corporations. In order to see the impact of these variables other forces of agglomeration such as distance to Western European markets and dispersion forces such as high wages are taken into account. Investigation is carried out on a small-to-medium sized European economy that has just gone through economic transition involving almost unprecedented rapid market liberalisation. A rich dataset of corporate tax returns of Hungarian firms between 1992 and 2002 as well as annual labor surveys are used to get location, sales and wage data. Various econometric specifications of both discrete choice and count data models are applied to provide robustness of results that may be crucial when working with firm level data.
Keywords: F23; R3; R12; C35; 330; economic geography; industrial location; FDI; regional policy; discrete choice models; Direktinvestition; Betriebliche Standortwahl; Regionalpolitik; Ungarn; Logit-Modell; Diskrete Entscheidung